The use of monoclonal antibody for the immunodiagnosis of Fasciola gigantica infection in cattle (1997)
Antigens that were specific to Fasciola gigantica were obtained from the whole worm homogenate of the parasite by immunoaffmity chromatography in cyanogen bromide-activated sepharose 4B columns and used for the production of monoclonal antibodies. The F. gigantica- specific monoclonal antibody was labelled with horseradish peroxidase and used for the detection of circulating antigen by the direct ELISA method in the sera of cattle experimentally infected with the parasite. Circulating antigens were detectable in the sera of the animals as from the third week after infection while negative absorbance values were obtained 2 weeks after the termination of the infection by chemotherapy with oxyclozanide. This immunodiagnostic method offers an attractive alternative as a supplement to the conventional. coprological diagnosis of fasciolosis